PUBLIC SPEAKING 5.0: EFFECTIVE COMMUNICATION TRAINING FOR GEN Z IN THE COMPETITIVE DIGITAL WORKPLACE - Ari Prabowo; Yahya Tanjung; Ananda Fitriani Dewi; Austin Alexander Parhusip; Taufiq Risal; Yusriadi (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
Public Speaking 5.0 Training is an activity aimed at improving effective communication skills in Gen Z in facing the increasingly dynamic digital workplace competition. This activity was held on Wednesday, April 7, 2026, at the Study Room (Aula). Gen Z is known as a generation close to technology, but not all have the courage and skills to speak in public in a structured, confident, and persuasive manner. This training equips participants with a basic understanding of public speaking, message-building techniques, body language usage, nervousness management, and the ability to convey ideas interestingly, both in person and through digital media. The activity method is carried out through material delivery, interactive discussions, presentation simulations, speaking practice, and providing direct feedback to participants. Through this activity, participants are expected to be able to increase self-confidence, think more critically, and build a positive personal branding. Public speaking skills are an important competency because today's workplace demands not only mastery of technology, but also communication, collaboration, and adaptation skills. Thus, this training is expected to shape Gen Z who are communicative, creative, professional, and ready to compete in the era of digital transformation.